ATRT-13. CANCER PREDISPOSITION AMONG CHILDREN WITH RHABDOID TUMORS: A SINGLE-CENTRE RETROSPECTIVE REVIEW. Issue 2 (22nd June 2018) - Coltin, Hallie; Pan, Anna; Malkin, David; Huang, Annie; Goudie, Catherine
Abstract: BACKGROUND: Rhabdoid tumor predisposition syndrome (RTPS) from SMARCB1 germline mutations must be ruled out in children with rhabdoid tumors (RT). The aim was to describe the diagnostic details of children with RT, genetic referral practices, and rates of SMARCB1 germline pathogenic mutations, and to compare clinical features of children with and without RTPS. METHODS: The medical charts of sequential children diagnosed with RT at the Hospital for Sick Children from 1995–2016 were reviewed for the diagnostic details, family histories, and genetic testing results. RESULTS: Fifty-nine children diagnosed with RT at a mean age of 37.6 months were included. Atypical teratoid rhabdoid tumors represented 73% of the tumors. Of the patients with family histories documented, 17% were suspicious for cancer predisposition. Of the 31 patients with genetic testing results, 12 had SMARCB1 pathogenic mutations. The mean age of diagnosis was 12.0 months for children with RTPS compared to 37.6 months in those without RTPS. In children presenting at ≤ 12 months of age, 64% were subsequently diagnosed with germline SMARCB1 mutations. When the age limit was increased to ≤ 36 months, the rate of SMARCB1 mutations was 42%, while this rate was 25% in those aged > 36 months. CONCLUSION: Rates of SMARCB1 germline mutations increase with younger age, but the elevated rates of RTPS detection in this cohort for all ages support the practice that all children diagnosed with RT should undergo genetic testing to investigate for RTPS, even if the family history is not suggestive of inherited cancer.